An exploratory cluster-randomized controlled trial on mindfulness yoga’s effectiveness in school-refusing children: reductions in SCAS-C physical injury fears and pulse rate - Kawazu, Suguru; Amitani, Marie; Suzuki, Hajime; Amitani, Haruka; Monuki, Takako; Wada, Midori; Toyohira, Satomi; Hamada, Kazumasa; Yamamoto, Takako; Yoshimura, Takuya; Mizuma, Kimiko; Nishida, Yuko; et al. (Frontiers in Human Neuroscience, 2024)
IntroductionSchool refusal is one of the serious problems with children’s mental health, and various studies have examined its prevalence and factors among students. Although many studies suggested that anxiety and depression are deeply associated with school refusal, there is little agreement as to effective interventions. The purpose of this paper is to evaluate the efficacy and safety of mindfulness yoga intervention in children with school refusal.MethodThis study is a multicenter, exploratory, open cluster-randomized controlled trial. 43 participants aged 10–15 years with school refusal were randomly assigned to a non-yoga group with treatment as usual (TAU) which includes cognitive behavioral therapy based on self-monitoring, or a yoga group (4-week mindfulness yoga program provided by video sessions + TAU). The primary outcome was symptoms of anxiety evaluated by Spence Children’s Anxiety Scale-Children (SCAS-C). Participants were assessed in four time periods: a 2-week baseline (Day −14), a baseline (Day 1), a post-test after 4 weeks of treatment (Day 29), and an 8-week follow-up (Day 85). Statistical analysis was conducted by a linear mixed effect model using SAS version 9.4.Results43 participants were included in the Full-analysis set (FAS) (21 in the mindfulness yoga group and 22 in the non-yoga group). The estimates of SCAS-C at post-test adjusted for baseline values in each treatment group were 39.9 in the mindfulness yoga group and 39.4 in the non-yoga group. The between-group difference for the estimates was 0.4 (80%CI −4.8 to −5.6, p = 0.54), which indicated mindfulness yoga program has no significant effect on anxiety compared with TAU. However, on an exploratory analysis of the subscale of SCAS-C, significant improvement was observed on the Physical Injury Fears subscale. The pulse rate was significantly lower in the yoga group compared to the non-yoga group.ConclusionThis study indicated the safety of a mindfulness yoga intervention for children with school refusal, but the effectiveness of the intervention for anxiety was limited. Further research is needed to determine the long-term effects of yoga and how it can best be integrated with other therapies.